2016
DOI: 10.1021/acsami.6b09775
|View full text |Cite
|
Sign up to set email alerts
|

Dual Core–Shell Structured Si@SiOx@C Nanocomposite Synthesized via a One-Step Pyrolysis Method as a Highly Stable Anode Material for Lithium-Ion Batteries

Abstract: Silicon (Si) has been regarded as a promising high-capacity anode material for developing advanced lithium-ion batteries (LIBs), but the practical application of Si anodes is still unsuccessful mainly due to the insufficient cyclability. To deal with this issue, we propose a new route to construct a dual core-shell structured Si@SiO@C nanocomposite by direct pyrolysis of poly(methyl methacrylate) (PMMA) polymer on the surface of Si nanoparticles. Since the PMMA polymers can be chemically bonded on the nano-Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…Besides pure Si, other Si‐based composites have also been investigated, such as nonstoichiometric SiO x and SiC. Similar to SiO x , SiO 2 and/or SiO can be reduced to Si in the initial lithiation process, which—accompanied by the generation of Li 2 O and Li 4 SiO 4 —act as buffer media to suppress the volume change and facilitate dispersion of Si in carbonaceous matrix to some extent . For instance, Yang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides pure Si, other Si‐based composites have also been investigated, such as nonstoichiometric SiO x and SiC. Similar to SiO x , SiO 2 and/or SiO can be reduced to Si in the initial lithiation process, which—accompanied by the generation of Li 2 O and Li 4 SiO 4 —act as buffer media to suppress the volume change and facilitate dispersion of Si in carbonaceous matrix to some extent . For instance, Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yang et al. reported that a Si@C@SiO 2 anode material with double core–shell structure exhibited higher reversible capacity and better cycling stability than a Si–C single core–shell composite . In addition, a few publications reported that SiC can also act as buffer backbone for enhancing the electronic conductivity of composite materials, although the initial reports revealed that SiC is electrochemically inactive toward lithium storage .…”
Section: Introductionmentioning
confidence: 99%
“…g) Cycle performance of the Si@void@C sphere anode at charge/discharge rates of C/5 and C/2 (1C = 4200 mAg À1 ); All experimental measurements were carried out at room temperature in two-electrode 2032 coin-type half cells . [16,17,19,44,47,52,53,55] As for Si@void@C (1565 and 1260 mAhg À1 at C/5 and C/2 after 1000 cycles), the performance is better than pomegranate structure (1160 mAhg À1 after 1000 cycles), [17] and Yolk-shell structure (1200 mAhg À1 after 1000 cycles). The linear portions at the low frequency region correspond to the diffusion of lithium ions in the composites.…”
Section: Electrochemical Performancementioning
confidence: 97%
“…For example, graphitic carbon anodes served in present LIBs technology have a theoretical capacity of only 372 mAh g −1 (corresponding to a saturated lithium composition of LiC 6 ) and poor Li‐ion transport rate (10 −12 –10 −14 cm 2 s −1 ) due to their regular arrangement of graphite layers . To address this capacity insufficiency of the anode, significant efforts have been devoted in the past decade to develop Li‐storable alloy anodes such as silicon, phosphorus, and tin as high‐capacity alternatives to graphitic anode. Though these alloy anodes can demonstrate extremely high Li storage capacities (4200 mAh g −1 for Li 4.4 Si, 2596 mAh g −1 for Li 3 P, and 994 mAh g −1 for Li 4.4 Sn), they suffer from poor cyclability and low coulombic efficiencies due to their huge volumetric changes during charge–discharge cycles.…”
Section: Introductionmentioning
confidence: 99%
“…
insufficiency of the anode, significant efforts have been devoted in the past decade to develop Li-storable alloy anodes such as silicon, [6][7][8][9] phosphorus, [10,11] and tin [12,13] as high-capacity alternatives to graphitic anode. Though these alloy anodes can demonstrate extremely high Li storage capacities (4200 mAh g −1 for Li 4.4 Si, 2596 mAh g −1 for Li 3 P, and 994 mAh g −1 for Li 4.4 Sn), they suffer from poor cyclability and low coulombic efficiencies due to their huge volumetric changes during charge-discharge cycles.In contrast to these alloy and graphite anodes, hard carbon (HC), [14][15][16][17] a nongraphitic carbon, seems to be a better option as a high capacity and high power anode for future LIB technologies.
…”
mentioning
confidence: 99%